ANALYSIS OF THE COOPERATION NETWORK WITHIN AN INNOVATION ECOSYSTEM IN THE INTERIOR OF SÃO PAULO STATE - Aguiar, Nívea Regina Marques; Mollo Neto, Mario (Seven Editora, 2026)
This research addresses the importance of cooperation networks between public, private, and third-sector institutions, driven by technological advancements and the need for agile responses to social and economic challenges. These networks favor the exchange of knowledge, the articulation of resources, and the collective construction of innovative solutions, especially in the fields of education, research, and innovation. In this context, innovation ecosystems emerge as interconnected environments that promote synergies among skills, infrastructure, and human capital, generating value and transforming territories. The research presented focuses on the Alta Paulista region, in São Paulo, and seeks to understand how cooperation networks are structured in education and innovation ecosystems. The study uses Social Network Analysis (SNA), supported by Netdraw® and UCINET® software, to map interactions, identify subgroups, and measure structural indicators. The methodology combines qualitative and quantitative approaches, characterizing itself as exploratory and descriptive, and includes document analysis and bibliographic review in scientific databases. The results reveal low density in the global network (0.011), indicating few connections relative to the existing potential, but higher density in the innovation sub-network (0.033), suggesting more exchanges, although still insufficient. The centrality of FSNTEDUC (55.8%) and FSNTPESQINOV (30.4%) highlights the strategic role of the Shunji Nishimura Foundation of Technology (FSNT) as an articulator in education, research, and innovation. In specific sub-networks, FSNTPESQINOV achieves centrality of 87.3%, reinforcing its influence on network dynamics. It is concluded that FSNT plays a central role in the Alta Paulista ecosystem, acting on several fronts—education, research, innovation, entrepreneurship, culture, and services—and consolidating itself as a strategic agent in the dissemination of information, coordination of projects, and strengthening of governance. Improving the network, with greater connectivity and stronger ties, can expand collaboration among actors, enhancing social, economic, and technological impacts, especially in agribusiness.